THE IMPACT OF DIVIDEND POLICY AND CAPITAL STRUCTURE ON FIRM VALUE IN AGRICULTURAL SECTOR - Luckyardi, Senny; Agustini, Kamelia; Nugraha, Nugraha; Sari, Maya (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2021)
This study aims to determine the effect of Dividend Policy and Capital Structure on Agricultural Sector’s Company Value. The research method used in this study is verification method with quantitative approach. The case study was conducted on agricultural sector companies listed on the Indonesia Stock Exchange in 2015-2019. The sample used is Price Book Value (PBV) and Debt to Equity Ratio (DER) in 14 agricultural sector companies obtained from Financial Statements published on the Indonesia Stock Exchange website: www.idx.co.id for the period 2015-2019. The results showed that the variables of Dividend Policy and Capital Structure had a negative and not significant effect on company value.